(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Phenomenological studies examine imagination as a dimension of language and explore the creative role of imagination in the creation of new meanings in language. This exploration has many implications in poetry where language is used creatively and new meanings emerge from the creative and unexpected use of language by the poet. This paper aims to describe a phenomenological account of imagination in poetry by introducing the concepts that appear most relevant to imagination in poetry within the domain of phenomenological studies. In order to do this, the study focuses on the main tenets of phenomenological studies relevant to imagination in poetry, namely the concepts of ‘metaphor’ and ‘intentionality’. The discussion highlights the level of creativity of imagination in poetry in comparison with the reduction of imagining to perceiving in language. Likewise, the poetic image in poetry is also introduced as animage which is not a resume of the old meanings of perception. Phenomenology of imagination in poeticcreationtakes us beyond the pervious analyses of the characteristics of imagination as a creative faculty and helps to establish a link between creativity, meaning and imagination.